2009
DOI: 10.1111/j.1600-0854.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

A Single Method for Cryofixation and Correlative Light, Electron Microscopy and Tomography of Zebrafish Embryos

Abstract: †These authors contributed equally to this work. The zebrafish is a powerful vertebrate system for cell and developmental studies. In this study, we have optimized methods for fast freezing and processing of zebrafish embryos for electron microscopy (EM). We show that in the absence of primary chemical fixation, excellent ultrastructure, preservation of green fluorescent protein (GFP) fluorescence, immunogold labelling and electron tomography can be obtained using a single technique involving high-pressure fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 23 publications
(22 reference statements)
1
118
1
1
Order By: Relevance
“…For future applications, the here presented workflow can be adapted to be used for other resin embedded samples, e.g. Lowicryls, which have already been used in correlative studies (Nixon et al ., 2009;Kukulski et al ., 2011; Lucas et al . 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For future applications, the here presented workflow can be adapted to be used for other resin embedded samples, e.g. Lowicryls, which have already been used in correlative studies (Nixon et al ., 2009;Kukulski et al ., 2011; Lucas et al . 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Further work using CLEM showed that vesicle budding appears to involve the assembly of clathrin adaptors (Skruzny et al, 2015) and the bending of a dynamic preassembled clathrin coat (Avinoam et al, 2015). Similar approaches of preserving the fluorescence signal have been used in CLEM of zebrafish embryos (Nixon et al, 2009), C. elegans (Watanabe et al, 2011) and mammalian cells (Paez-Segala et al, 2015;Peddie et al, 2014). CLEM can also be performed thanks to the development of bimodal probes, such as the mini singlet oxygen generator (miniSOG) (Shu et al, 2011) and proteins of the ascorbate peroxidase (APX) family, in particular APEX2 (Lam et al, 2015).…”
Section: Ground-breaking In Vitro Clemmentioning
confidence: 99%
“…Although many advances have been made in sample preparation for correlative microscopy, most protocols require processing or staining of the specimen in between the transfer from the FM to the EM (Roessler et al 1991;Ren et al 2003;van Rijnsoever et al 2008;Watanabe et al 2011;Kopek et al 2012). Protocols yielding resin-embedded specimens that can be imaged both with FM and TEM were recently developed (Nixon et al 2009;Kukulski et al 2011;. However, correlative imaging of …”
Section: Sample Preparation For Correlative Microscopymentioning
confidence: 99%